2020
DOI: 10.1186/s10194-020-01094-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid referral for headache management from emergency department to headache centre: four years data

Abstract: Background Headache is one of the most common reason for medical consultation to emergency department (ED). The inappropriate use of ED for non-emergency conditions is a problem in terms of overcrowding of emergency facilities, unnecessary testing and treatment, increased medical costs, burden on medical service providers and weaker relationships between patient and primary care provider. The aim of this study was to analyze the different stages of ED management of headache to identify those de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…The extent to which CT scans are performed in headache patients at emergency rooms worldwide varies widely (27-75%) (11)(12)(13)(14). Overall, previous research showed a similar low-threshold tendency to perform neuroimaging in the ED setting in both adults and children, with low diagnostic yield (12,(15)(16)(17)(18). Our finding of intracranial pathology in 13% of cranial CT scans is in accordance with results presented in previous studies (19)(20)(21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The extent to which CT scans are performed in headache patients at emergency rooms worldwide varies widely (27-75%) (11)(12)(13)(14). Overall, previous research showed a similar low-threshold tendency to perform neuroimaging in the ED setting in both adults and children, with low diagnostic yield (12,(15)(16)(17)(18). Our finding of intracranial pathology in 13% of cranial CT scans is in accordance with results presented in previous studies (19)(20)(21).…”
Section: Discussionsupporting
confidence: 89%
“…As shown previously, abnormal CT results are rare in headache patients without neurological deficits (10). The extent to which CT scans are performed in headache patients at emergency rooms worldwide varies widely (27-75%) (11)(12)(13)(14). Overall, previous research showed a similar low-threshold tendency to perform neuroimaging in the ED setting in both adults and children, with low diagnostic yield (12,(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 64%
“…1 rapid referral to a headache clinic or specialist after ruling out severe or life-threatening secondary headache by ED physicians could help patients receive a more accurate diagnosis and appropriate treatment while reducing ED resource utilization at the same time. 18,19 Our study found that more than one-third and opioids (17.6%), whereas triptans were not received by any of those patients (n = 244). 18 Another study, which was conducted in China, reported that 7.1% of patients with migraine received opioids as acute mediations despite of the fact that opioids are subject to government regulation in China.…”
Section: Discussionmentioning
confidence: 65%
“…18,19 Our study found that more than one-third and opioids (17.6%), whereas triptans were not received by any of those patients (n = 244). 18 Another study, which was conducted in China, reported that 7.1% of patients with migraine received opioids as acute mediations despite of the fact that opioids are subject to government regulation in China. 21 It is important to note that the migraine treatment guidelines from US, Europe, and China all clearly discourage the use of opioids for acute treatment due to limited efficacy and concern of overuse.…”
Section: Discussionmentioning
confidence: 65%
“…Универсальность этого класса лекарственных средств в лечении ГБ связана с большим опытом их применения, изученностью и наличием рандомизированных контролируемых исследований (РКИ) при всех первичных цефалгиях. Например, среди пациентов с жалобами на ГБ в итальянской университетской больнице (за период наблюдения 4 года) чаще всего врачи назначали НПВП -в 44,3% случаев, реже -опиоиды (17,6%), тогда как парацетамол -только в 8,2% случаев [35]. В исследовании, проведенном во Франции, НПВП назначались наиболее часто (в 42,9% случаев), реже врачи выписывали опиоидные анальгетики (9,1%), противорвотные (8%) и противотревожные препараты (3%) [36].…”
Section: принципы использования нестероидных противовоспалительных препаратов в купировании рецидивирующих гбunclassified